2021
DOI: 10.3390/ijms22031228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine Has Extrathyroidal Effects as an Antioxidant, Differentiator, and Immunomodulator

Abstract: Most investigations of iodine metabolism in humans and animals have focused on its role in thyroid function. However, considerable evidence indicates that iodine could also be implicated in the physiopathology of other organs. We review the literature that shows that molecular iodine (I2) exerts multiple and complex actions on the organs that capture it, not including its effects as part of thyroid hormones. This chemical form of iodine is internalized by a facilitated diffusion system that is evolutionary con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 93 publications
1
29
0
5
Order By: Relevance
“…It is well established that the primary mechanism of CFF is the induction of p53 apoptosis via DNA adducts formation [11]. Conversely, I 2 actions are more complex since this halogen could act directly on mitochondria by inducing an apoptosis cascade [12], or indirectly by activating PPARγ and triggering redifferentiation or apoptotic signaling [7,13]. Our results showed that both components (I 2 and CFF) increased apoptosis (exposure of annexin-Cy5 and low expression of SVV), but only I 2 groups modified master differentiation genes, decreasing the expression of MYCN, and significantly inducing PPARγ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the primary mechanism of CFF is the induction of p53 apoptosis via DNA adducts formation [11]. Conversely, I 2 actions are more complex since this halogen could act directly on mitochondria by inducing an apoptosis cascade [12], or indirectly by activating PPARγ and triggering redifferentiation or apoptotic signaling [7,13]. Our results showed that both components (I 2 and CFF) increased apoptosis (exposure of annexin-Cy5 and low expression of SVV), but only I 2 groups modified master differentiation genes, decreasing the expression of MYCN, and significantly inducing PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the antineoplastic effects of molecular iodine (I 2 ) are well established, triggering apoptotic and redifferentiation mechanisms in several cancer cells, including mammary, ovary, and prostate, among others [7]. These effects are mediated partially by the activation of peroxisome proliferator-activated receptors type gamma (PPARγ) and directly, as a mitocan element, by thiol depletion and disruption of the mitochondrial membrane potential (Mmp), triggering the intrinsic apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Iodine role in prostate physiology is still poorly understood, however, it was shown that I ‐ is taken up by prostatic epithelial cells through sodium/iodide symporter (NIS). In men with low‐grade BPH supplementation with Lugol solution for 8 months improved urinary tract symptoms and lead to serum PSA reduction (Aceves et al., 2021). In rat model of BPH, amino acid‐bound and inorganic iodine also exerted antihyperplastic action (Bespalov et al., 2019; Quintero‐García et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no unequivocal association between iodine deficiency and the risk of prostate disease, thyroid disorders have been shown to significantly increase the risk of developing this pathology (Hoption Cann et al., 2007). In addition, there is evidence that iodine‐rich diet may reduce the risk of BPH (Aceves et al., 2021). It is suggested that free iodine, which is not incorporated into thyroid hormones, may have antioxidant and anti‐inflammatory effects, as well as regulating cell differentiation and proliferation (Aceves et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation